Experimental data suggest between population reversal in the condition dependence of two sexually selected traits - Gergely Hegyi; Miklós Laczi; Gyula Szabó; Dóra Kötél; Fanni Sarkadi; János Török (Scientific Reports)
Abstract When viewing mate choice as a process of adaptive evolution, the condition-dependence of sexual ornaments represents a central pillar. Experimental tests of condition-dependence are few and refer to one population per species. The first brood size manipulation experiment aimed to test ornament condition-dependence had been reported from a Swedish population of collared flycatchers. Here we report a similar experiment conducted in a Hungarian population, examining the change of white plumage patch sizes of male parents by the next year and the patch sizes of male offspring in adulthood. The results consistently indicate that experimentally modified reproductive effort affects male wing, but not forehead patch size. To the contrary, previous results from the Swedish population indicated significant effects on forehead, but not wing patch sizes. Both patches are sexually selected in both populations, so the diverging results offer the first experimental suggestion of a trait by population crossover in the information content of two sexual ornaments. We conclude that explaining why some ornaments are condition-dependent is still far ahead, and further, preferably experimental population comparisons would be helpful.